Cover Picture: Time‐Dependent Diaryl Ether Inhibitors of InhA: Structure–Activity Relationship Studies of Enzyme Inhibition, Antibacterial Activity, and in vivo Efficacy (ChemMedChem 4/2014). Issue 4 (April 2014) - Pan, Pan; Knudson, Susan E.; Bommineni, Gopal R.; Li, Huei‐Jiun; Lai, Cheng‐Tsung; Liu, Nina; Garcia‐Diaz, Miguel; Simmerling, Carlos; Patil, Sachindra S.; Slayden, Richard A.; Tonge, Peter J.
<x xml:space="preserve">Abstract</x> The front cover picture illustrates the role of drug–target residence time in drug candidate selection. Although traditional lead optimization relies primarily on structure–activity relationships from thermodynamic parameters, drug–target residence time will also impact drug efficacy since drug concentration is not constant in vivo. Here, a structure–kinetics relationship for the inhibition of InhA, the Mycobacterium tuberculosis enoyl‐ACP reductase, is reported. Two time‐dependent inhibitors of InhA caused a significant decrease in bacterial load in a mouse model of tuberculosis infection, in contrast to a rapid reversible inhibitor that showed no effect, further validating residence time as a metric for predicting drug efficacy. For further details, see the Full Paper by Peter J. Tonge, Richard A. Slayden et al. on p. 776 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>